Film jako narzędzie pomocnicze w procesie adaptacji migrantów – imigrantów i uchodźców - Agnieszka Tambor (Postscriptum Polonistyczne)
Film is one of the media which, due to their accessibility and popularity, can be easily used in today’s world as a tool supporting integration and the process of integration into a foreign culture, which is often very distant (geographically and mentally). The paper is based on the assumption that a foreign culture cannot be learned, but that one can get to know it and to learn as much as possible “about it”. The aim of the text is to indicate which criteria should be taken into account when selecting films intended for immigrants and refugees, and how these films may support the process of adaptation to the Polish culture.